Protocol-driven primary care and community linkage to reduce all-cause mortality in rural Zambia: a stepped-wedge cluster randomized trial - Mutale, Wilbroad; Ayles, Helen; Lewis, James; Bosompraph, Samuel; Chilengi, Roma; Tembo, Margaret M.; Sharp, Ab; Chintu, Namwinga; Stringer, Jeffrey (Frontiers in Public Health, 2023)
Introduction: While tremendous progress has been made in recent years to improve the health of people living in low- and middle-income countries , significant challenges remain. Chief among these are poor health systems Methods: BHOMA was a complex health system intervention comprising intensive clinical training and quality improvement measures, support for commodities procurement, improved community outreach, and district level management support. The intervention was introduced as a stepped wedge cluster-randomised trial in 42 predominately rural health centers and their surrounding communities in Lusaka Province, Zambia. We conducted the study between 2011 and 2015 .The primary outcome was all-cause mortality among those between 28 days and 60 years of age . We fit Cox proportional hazards model with shared frailty at the cluster level for the primary analysis. Results: Mortality declined substantially from 3.9 per 1000 person-years in the pre-intervention period, to 1.5 per 1000 person-years in the post intervention period. When we compared intervention and control periods , there were 174 deaths in 49,230 person years (age-standardised rate=4.4 per 1000 person-years) in the control phase and 277 deaths in 74,519 person years (age-standardised rate=4.6 per 1000 person-years) in the intervention phase. Overall, there was no evidence for an effect of the intervention in minimally-adjusted (hazard ratio [HR] = 1.18; 95% confidence interval [CI]: 0.88, 1.56; p-value=0.265), or adjusted (HR = 1.12; 95% CI: 0.84, 1.49; p-value=0.443) analyses. Coverage scores that showed some evidence of changing with time since the cluster joined the intervention were: an increasing proportion of children sleeping under insecticide treated bed-net (p-value<0.001); an increasing proportion of febrile children who received appropriate anti-malarial drugs (p-value=0.039); and an increasing proportion of ever hypertensive adults with currently controlled hypertension (p-value=0.047). No adjustments were made for multiple-testing and the overall coverage score showed no statistical evidence for a change over time (p-value=0.308). Conclusion: We noted an overall reduction in post-neonatal under 60 mortality in the study communities during the period of our study, but this could not be attributed to the BHOMA intervention.Improvements in service coverage scores were observed.